Experimental study on erosion resistance evaluation of single-layer metal mesh screen. (November 2021) - Wu, Lijuan; Ying, Ruomeng; Lou, Yishan; Shi, Baocheng; Zhang, Xingkai; Qiu, Yijie; Zhang, Yindi
In order to predict the erosion life and erosion failure time of the metal mesh, based on the rotating erosion experiments under different working conditions, the erosion mass loss of the metal mesh under different factors was measured by the weight loss method and the erosion mathematical prediction model was put forward. The erosion wear mechanism of the single-layer metal mesh was explored by using electron microscope scanner and optical microscope. The results show that the erosion rate increases exponentially with the increase of liquid velocity (0.5, 1.0, 1.5, 2.0 m/s). When the solid mass fraction (0.3%, 0.5%, 0.8%) and erosion Angle is 15°–45°, the erosion rate is proportional to the solid mass fraction and erosion Angle. After erosion, the mesh samples suffered different degree of pitting corrosion, ploughing and cutting wear, and the mesh wear was local wear. Compared with the experimental value, the error of the erosion mathematical model is less than 20%, which has a certain reliability, and has an important reference significance for guiding the production control of sand oil Wells.